Ethnocultural values of the peoples of Kabardino-Balkaria as an element of soft power in interna-tional relations of the Russian Federation (based on the example of the activities of the Interna-tional Circassian association for the popularization of Circassian ethnic culture) - Anzor V., Kushkhabiev (Kavkazologiya, 2024)
It has been revealed that the popularization of the Circassian ethnic culture, propaganda of the components of the ideological position – maintaining interethnic peace and a positive image of Russia abroad is one of the main directions in the activities of the International Circassian Associ-ation. In this activity of the ICA, the most large-scale and effective are socio-cultural forums, sci-entific and practical conferences, festivals, educational projects, etc. These aspects of the ICA’s activities are also released as part of the work with young compatriots and repatriates. The com-ponents of the ideological position of the ICA are recorded in the resolutions of its XIII and XIV congresses. Considerable attention in the activities of the ICA is paid to events aimed at popular-izing the Circassian language (Adyghe and Kabardino-Circassian literary languages) and attract-ing public attention to the problems of its preservation. The active and constructive work of the ICA was highly appreciated at the federal level. In the welcoming address of the President of the Russian Federation V.V. Putin to the participants and guests of the XIII Congress of the ICA, it was recorded that the ICA cares about preserving and popularizing the native language, implements meaningful projects in the field of culture, edu-cation, enlightenment, increases multifaceted interaction with foreign compatriots, that the ICA’s efforts to maintain peace and consent in the North Caucasus. In 2023 ICA was included in the Fed-eral Register “All-Russian Book of Honor”, in which the most worthy organizations of various forms of ownership and fields of activity are formed.